Educating Students Understanding Of Student Nutritional Status Measurement Through School Health Education - Sulistyo, Yully Wahyu; Ma’arif, Ilmul; Hendrawan, Kahan Tony (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
In the era of technological development, the condition of the student's body is an important concern in human life, one of which is the movement activity carried out every day and must also have a food consumption pattern, because it is a strong foundation for maintaining health in each individual. So that the material in this education is designed to be interesting and easy to understand in an effort to be able to provide students with knowledge and understanding of the nutritional status of students, this service method uses the Participatory Action Research (PAR) approach which aims as learning in the process of overcoming problems and also as a practical need and also the production of science, physical education study programme students at PGRI University Jombang who take school health education courses as participants in activities. The results of this service show that the results give positive things from the results of using two indicators including knowledge of nutritional status and understanding of nutritional status measurements explain in the good category.